2019
DOI: 10.1111/head.13588
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Acute Treatment Needs From the 2017 Migraine in America Symptoms and Treatment Study

Abstract: Objectives To characterize unmet treatment needs in a sample of Migraine in America Symptoms and Treatment (MAST) Study participants using oral, acute prescription migraine medications. Background The MAST Study is a 2017 study of US adults with migraine that profiles current treatment patterns and identifies and quantifies unmet treatment needs. Methods Cross‐sectional data from an online survey of US adults meeting ICHD‐3 beta criteria for migraine. For inclusion in this paper, respondents self‐reported a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 44 publications
1
66
0
3
Order By: Relevance
“…Efficacy was evaluated for subgroups based on a specific patient, migraine disease, and attack characteristics that have been historically associated with reduced efficacy of acute treatment (“difficult‐to‐treat”). Analyses included the following subgroups of patients: ≥24 headache days in past 3 months, history of migraine ≥20 years, severe disability based on MIDAS score ≥21, 31 obesity 4,18 (BMI ≥30 kg/m 2 ), history of psychiatric disorder (depression, bipolar disorder, anxiety, sleep disorders, and/or post‐traumatic stress disorder), 4,31 rapidly escalating attack (headache progressed to moderate‐to‐severe headache intensity within 60 minutes from pain onset), 32 severe headache at the time of treatment, 32 co‐existence of nausea at the time of treatment, delayed treatment 31,32 (patients who initiated treatment at >2 and ≥4 hours post‐onset of attack), and patients with patient‐reported migraine‐related functional disability defined as “needs complete bed rest” at the time of treatment 5,31 …”
Section: Methodsmentioning
confidence: 99%
“…Efficacy was evaluated for subgroups based on a specific patient, migraine disease, and attack characteristics that have been historically associated with reduced efficacy of acute treatment (“difficult‐to‐treat”). Analyses included the following subgroups of patients: ≥24 headache days in past 3 months, history of migraine ≥20 years, severe disability based on MIDAS score ≥21, 31 obesity 4,18 (BMI ≥30 kg/m 2 ), history of psychiatric disorder (depression, bipolar disorder, anxiety, sleep disorders, and/or post‐traumatic stress disorder), 4,31 rapidly escalating attack (headache progressed to moderate‐to‐severe headache intensity within 60 minutes from pain onset), 32 severe headache at the time of treatment, 32 co‐existence of nausea at the time of treatment, delayed treatment 31,32 (patients who initiated treatment at >2 and ≥4 hours post‐onset of attack), and patients with patient‐reported migraine‐related functional disability defined as “needs complete bed rest” at the time of treatment 5,31 …”
Section: Methodsmentioning
confidence: 99%
“…Many people with migraine have treatment management gaps, including high levels of migraine‐associated disability and dissatisfaction with the efficacy and/or tolerability of their current acute treatment regimen . Currently available medications for the acute treatment of migraine attacks may be ineffective or poorly tolerated in some patients and are contraindicated in people with certain cardiovascular comorbidities .…”
Section: Introductionmentioning
confidence: 99%
“…Currently available medications for the acute treatment of migraine attacks may be ineffective or poorly tolerated in some patients and are contraindicated in people with certain cardiovascular comorbidities . The recently conducted 2017 Migraine in America Symptoms and Treatment Study demonstrated that 95.8% of respondents with migraine (inclusion criteria: at least 3 monthly headache days in the past 3 months and at least 1 headache day in the past 30 days) who were currently taking an oral acute prescription medication for headache had at least 1 unmet need; the most common attack‐related unmet needs were rapid onset (65.3%) and disability (55.6%) . New migraine‐specific acute medications that reduce headache‐related disability may provide more treatment options with increased satisfaction for people with migraine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the pain-free response at 2 hours for frovatriptan 2.5 mg as the clinical endpoint, unilateral pain, presence of phonophobia, presence of one or more cranial autonomic symptoms, and presence of one or more premonitory symptom were each associated with that outcome. Patients and physicians want better ways to associate their treatments with outcomes and are largely unsatisfied with current prescription therapies (19,20). So far, some studies have identified migraine features associated with (poor) triptan efficacy (7,8).…”
Section: Discussionmentioning
confidence: 99%